Section 1.1 Détermination par l'algèbre
¶Exercice 1.1.1.
Déterminez les limites suivantes à l'aide de l'algèbre.
\(\displaystyle\lim_{x\rightarrow -1}\frac{x+1}{x^2+2x+1}\)
\(\displaystyle\lim_{x\rightarrow -1}\frac{2x^4+4x^2+2x^3+3x-1}{-2x^2+3x+5}\)
\(\displaystyle\lim_{x\rightarrow 4}\frac{4-x}{\sqrt{4x}-4}\)
\(\displaystyle\lim_{x\rightarrow 8}\frac{\frac{1}{3}-\frac{x}{24}}{x^2-64}\)
\(\displaystyle\lim_{x\rightarrow +\infty}\frac{7x^2+2x^2-1}{5-28x^4}\)
\(\displaystyle\lim_{x\rightarrow -\infty}\frac{x^2+4x-12}{2x^3-7x^2+7x-2}\)
\(\displaystyle\lim_{x\rightarrow 1^+}\frac{3}{(x-1)^2}-\frac{2}{x-1}\)
\(\displaystyle\lim_{x\rightarrow +\infty}\frac{\sqrt{4x^2-1}}{x+2}\)
\(\displaystyle\lim_{x\rightarrow -\infty}\frac{12x+7}{\sqrt{9x^2+1}}\)
\(\displaystyle\lim_{x\rightarrow 3}\frac{x^2-5x+6}{|x-3|}\)
\(\displaystyle\lim_{x\rightarrow 3}\frac{x-3}{\sqrt{x+6}}\)
\(\displaystyle\lim_{x\rightarrow -1^-}\frac{x+1}{x^2+2x+1}=-\infty\) et \(\displaystyle\lim_{x\rightarrow -1^+}\frac{x+1}{x^2+2x+1}=+\infty\)
\(\displaystyle -1\)
\(\displaystyle -2\)
\(\displaystyle -\frac{1}{384}\)
\(\displaystyle -\frac{1}{4}\)
\(\displaystyle 0\)
\(\displaystyle +\infty\)
\(\displaystyle 2\)
\(\displaystyle -4\)
\(\displaystyle\lim_{x\rightarrow 3^-}\frac{x^2-5x+6}{|x-3|}=-1\) et \(\displaystyle\lim_{x\rightarrow 3^+}\frac{x^2-5x+6}{|x-3|}=1\)
\(\displaystyle 0\)